2020
DOI: 10.1038/s41366-019-0511-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of The Daily Mile on childhood weight outcomes and wellbeing: a cluster randomised controlled trial

Abstract: Background The Daily Mile is designed to increase physical activity levels with children running or walking around school grounds for 15-min daily. It has been adopted by schools worldwide and endorsed as a solution to tackle obesity, despite no robust evidence of its benefits. We conducted a cluster randomised controlled trial to determine its clinical and costeffectiveness. Methods Forty schools were randomly assigned (1:1) to either the Daily Mile intervention or control group in which only the usual school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(84 citation statements)
references
References 33 publications
2
79
0
Order By: Relevance
“…That is, participants in TDM schools demonstrated a significant decrease in PA levels from baseline to follow up (8 months later), while participants at ASF schools experienced an opposing trajectory and demonstrated a significant increase in PA levels over the same timeframe. Results relating to participants at TDM schools present as being in line with those of Breheny et al (2020) who suggest that The Daily Mile initiative is beneficial in the immediate (i.e. within the first 4 -6 months) but does not sustain interest (from either the teachers and/or children) over time.…”
Section: Discussionsupporting
confidence: 71%
“…That is, participants in TDM schools demonstrated a significant decrease in PA levels from baseline to follow up (8 months later), while participants at ASF schools experienced an opposing trajectory and demonstrated a significant increase in PA levels over the same timeframe. Results relating to participants at TDM schools present as being in line with those of Breheny et al (2020) who suggest that The Daily Mile initiative is beneficial in the immediate (i.e. within the first 4 -6 months) but does not sustain interest (from either the teachers and/or children) over time.…”
Section: Discussionsupporting
confidence: 71%
“…It appears to be a wide-reaching intervention reaching high-performing and low-performing primary schools alike and local authority areas with better and poorer health. If it can be assumed that the physical fitness benefits of TDM seen in small trials to date are sustainable, 14 15 17 then our findings that it is taken up by urban schools serving disadvantaged school populations suggest added value from TDM over other interventions, that when scaled have failed to reach populations of children most in need. 39…”
Section: Discussionmentioning
confidence: 92%
“…12 13 A growing evidence base suggests that TDM increases physical activity and fitness over the first 12 months of its adoption, 14 15 but evidence of its impact on educational performance, well-being or maintaining healthy weight is limited. 16 17…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, current evidence on the chronic effects of The Daily Mile on children’s cardiorespiratory fitness is contradictory. While some studies found improvements to cardiorespiratory fitness at 12 weeks 54 56 , others reported no effects to cardiorespiratory fitness following six 57 or 12 months of participation 58 . Future research could thus consider whether making adaptations to The Daily Mile and/or implementing a different activity may be more successful in contributing to these targets and improving cardiorespiratory fitness in both sexes.…”
Section: Discussionmentioning
confidence: 98%